Antarctic ice sheet palaeo-thinning rates from vertical transects of cosmogenic exposure ages. (15th February 2019) - Small, David; Bentley, Michael J.; Jones, R. Selwyn; Pittard, Mark L.; Whitehouse, Pippa L.
Abstract: Constraining Antarctic ice sheet evolution provides a way to validate numerical ice sheet models that aid predictions of sea-level rise. In this paper we collate cosmogenic exposure ages from exposed nunataks in Antarctica that have been used, or have the potential to be used, to constrain rates of thinning of the Antarctic Ice Sheets since the Last Glacial Maximum. We undertake quality control of the data and adopt a Bayesian approach to outlier detection. Past thinning rates are modelled by Monte Carlo linear regression analysis. We present thinning rates from 23 sites across Antarctica. The resulting data set is the first Antarctic-wide collation of past ice sheet thinning rates and provides an empirical starting point for future model-data comparisons. Palaeo-thinning rates are spatially variable with high rates appearing to correlate to areas of contemporary rapid changes. On centennial timescales past thinning rates are comparable to modern day observations implying that modern day thinning has the potential to persist for centuries in numerous parts of Antarctica. The onset of abrupt thinning from all sites post-dates Meltwater Pulse 1A suggesting that its source region(s) are distal to areas where exposure age constraints on ice surface geometry exist. Highlights: Exposure ages that constrain ice sheet thickness collated from an online database. Thinning rates are reconstructed from 23 sites across Antarctica. Palaeo-thinning rates are comparable to modern observations. Wide-spread thinning during the Holocene, but after Meltwater Pulse 1A.